Increasing the Brand Awareness of PT. Hadi Citra Cemerlang by Emphasizing Its Unique Selling Point in a Marketing Booklet - Edwan Dhika Dwijayaputra Liew (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
PT. Hadi Citra Cemerlang is a frozen food distributor in East Java, Indonesia. The company’s target markets are restaurants, Agencies, and Convenience stores. As one of the biggest distributors in East Java, PT. Hadi Citra Cemerlang has problem. The company has difficulty in selling its products and introducing the uniqueness of the company. Therefore, PT. Hadi Citra Cemerlang needs to increase its brand awareness through a promotional tool. The writer provides a solution which is a Marketing Booklet. The writer will use the theory of branding, promotional tool, marketing booklet, and Unique Selling Point (USP) to make that happen. After identifying the company's Unique Selling Point, the USP will be highlighted and emphasized in the marketing booklet. Excellence services and Lower prices are the main USP of the company. A marketing booklet can benefit the company since it can help prospects, new customers easier and more efficiently. Keywords: marketing booklet, unique selling point, promotion, promotional tool